Social Behavior and Skills in Children - Matson, Johnny L. (Springer New York : Imprint: Springer, 2009)
That children are capable of pathology-not only such conditions as ADHD and learning disabilities, but also such "adult" disorders as anxiety and depression-stands as a defining moment in psychology's recent history. Within this recognition is the understanding that the social skills deficits that accompany these disorders must be targeted for assessment and treatment to ensure optimal functioning in school, with peers, and in later transitions to puberty and adulthood. Social Behavior and Skills in Children cuts across disciplinary lines to clarify the scope of assessment options and interventions for a wide range of disorders. A panel of leading scholars reviews current research, discusses social deficits unique to specific disorders, and identifies evidence-based best practices in one authoritative, approachable reference. This volume: Discusses theoretical models of social skills as they relate to assessment and treatment. Analyzes the etiology of social behavior problems in children and the relation between these problems and psychopathology. Reviews 48 norm-referenced measures of social skills in children. Examines the range of evidence-based social skills interventions. Addresses challenging behaviors, such as aggression and self-injury. Focuses on specific conditions, including developmental disabilities, conduct disorders, ADHD, chronic medical illness, depression, anxiety, and severe psychopathology. Social Behavior and Skills in Children is an essential reference for university libraries as well as a must-have volume for researchers, graduate students, and clinicians in child, and school psychology, special education, and other related fields.